Histopathology and morphometric indices of the state of the carpal joint tissues in case of ischaemic osteonecrosis of the lunate bone (Kienbock’s disease) - Hryhorovskyi, Valeriy; Strafun, Sergey; Timoshenko, Sergey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The purpose of the present research was to reveal the intensity of pathomorphological changes in tissues of the carpal joint, which are observed in ischaemic osteonecrosis of the lunate bone (IONLB, Kienböck’s disease) and result in osteoarthrosis of the carpal joint, as well as their frequency and correlation dependences in the dynamics of osteoarthrosis formation owing to IONLB. As the material of the study, biopsies and resectates of the carpal bones from 20 patients with IONLB were used. It was found out that IONLB of the carpal bones was characterized by presence of persisting foci of lesion with a perifocal area of organization and reconstruction of the osseous tissue. Probably, as result of the injury effect, ischaemic necrosis foci could develop in the scaphoid and triquetrous bones rather than in the lunate one only. The articular cartilage in the bones, where ischaemic osteomedullary necrosis developed, as well as in the adjacent carpal bones remained vital, though underwent dystrophic-destructive changes, which corresponded to osteoarthrosis stages I-II. In the majority of IONLB patients the lesion of their carpal bones was accompanied by nonspecific synovitis of the joint, particularly with resultant fibrosis of the articular capsule layers. Positive moderate correlation dependences were revealed between the osteoarthrosis intensity degree of the carpal bones, adjacent to the affected one, and the activity of synovitis, as well as between the intensity of hypertrophy and hyperplasia of the synovial layer and the activity of synovitis.